A class of reconfigurable deployable platonic mechanisms. (November 2016) - Li, Ruiming; Yao, Yan-an; Kong, Xianwen
Abstract: This paper deals with the design of a new class of reconfigurable deployable Platonic mechanisms (RDPMs). At first, reconfigurable angulated element (RAE) with four half-platforms is designed and analyzed based on the reconfigurable property of angulated element. Using RAE as module, a method of synthesizing RDPMs is then proposed and three RDPMs are constructed. Starting from Type I generalised angulated element (GAE), a reconfigurable generalised angulated element (RGAE) comprised of two GAEs is investigated with its reconfigurable conditions identified. n pairs of straight elements (SE) and n pairs of angulated elements (AE) are further inserted into 2-RGAEs to construct n -SEs-2-RGAEs and n -AEs-2-RGAEs. The fully-retracted state and fully-expanded state of n -SEs-2-RGAEs and n -AEs-2-RGAEs are also detailed. Using 1-AE-2-RGAEs, three RDPMs with large magnification ratio are constructed in 3D software and fabricated using aluminum to verify their feasibility. This work provides a systematic approach to the design of RDPMs which can switch between two kinds of conventional deployable polyhedral mechanisms, including deployable polyhedral mechanisms with radially reciprocating motion and Hoberman spheres. Graphical abstract: Highlights: Reconfigurable angulated elements based on four half platforms are designed. The fully-retracted state and fully-expanded state of n -AEs-2-RGAEs are obtained. A family of reconfigurable deployable platonic mechanisms is constructed. A method of measuring the magnification ratios of RDPMs is given.